NUCLEOTIDE SEQUENCES OF mtDNA ENCODING GENES tRNA-Phe AND 12S rRNA WHICH HAS PURE CATARACT AND DIABETES MELLITUS TIPE II ASSOCIATED TO CATARACT PHENOTYPES - Ilhamuddin
Cataract is the main cause of blindness, which can be formed as a primary disease (pure cataract) and as a secondary disease as a complication of sistemic diseases, such as Diabetes Mellitus (DM). Both of cataract and DM are still the major health problem in Indonesia. The increasing of morbidity and mortality due to DM, makes this problem worse. This affects human life quality. Ethiology and pathogenesis of those diseases are still investigated, including mitochondrial dysfunction as an energy producer (in a form of ATP). Decreasing of its function at the molecular level can be caused by mutations in mitochondrial DNA (mtDNA). Previous study shows that there are several various sequences of mtDNA of the pure cataract phenotype and the DM type II associated with cataract, compared with revised Cambridge Reference Sequence (rCRS). Generally, these differences are conserved for both phenotypes, either in the form of homoplasmy or heteroplasmy. Up to date, molecular correlation between mtDNA mutation and both disease are still unclear. There are 87 samples collection, consisting of cataract lens and urine speciment from both phenotypes. Only 16 of them have been investigated. Therefore, this research is aim to analyze the variation between mtDNA sequences of both disease, using rRCS and the normal phenotype as standards. This research is focused on tRNA-Phe and 12S rRNA encoding genes of mtDNA.